A current collector, negative electrode and preparation and application thereof for metal lithium battery

By setting rectangular channels on the planar metal current collector of the lithium metal battery and coating the insulating layer, the problem of instability of lithium dendrites and SEI films is solved, and stable cycling performance and safety under high current density are achieved.

CN110875478BActive Publication Date: 2025-04-15CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201810999143.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2018-08-29
Publication Date
2025-04-15
Estimated Expiration
2038-08-29

AI Technical Summary

Technical Problem

Existing lithium metal batteries are prone to instability in lithium dendrites and SEI films, resulting in poor battery performance, especially the cycling performance under high current density is difficult to meet the needs of practical applications.

Method used

Using a planar metal current collector, by setting a plurality of rectangular channels through the thickness direction, and coating the insulating layers A and B on the surface and long surface of the channel, the apparent current density is reduced and the metal lithium growth interface is regulated to avoid extrusion and rupture of the SEI film.

Benefits of technology

It significantly improves the electrical performance of lithium metal batteries, especially the cycling performance at high current density, extends the battery's cycle life and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110875478B_ABST
    Figure CN110875478B_ABST
Patent Text Reader

Abstract

The present invention discloses a metal lithium negative electrode for a high-energy secondary lithium battery. The metal lithium negative electrode comprises a planar metal current collector, the planar metal current collector has a first surface and a second surface; the planar metal current collector is provided with a plurality of channels that penetrate the first surface and the second surface and are independent of each other, and the cross-section of the channels is rectangular; the metal on the first surface and / or the second surface of the planar metal current collector is composited with an insulating layer A, and the metal on any two opposite surfaces in the channel is composited with an insulating layer B. The insulating layer covering the long surface of the rectangular micron channel is conducive to the deposition of metal lithium on the wide surface of the micron channel, and is conducive to ensuring that the SEI film floats up and down on the wide surface during the deposition and dissolution of metal lithium, thereby avoiding the extrusion and rupture of the SEI film during the deposition and dissolution of lithium. The metal lithium negative electrode designed in this way can achieve ultra-stable and ultra-long-term cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy storage materials, and in particular relates to a metal lithium negative electrode for a high-energy secondary lithium battery. Background Art

[0002] Lithium metal is an ideal material for secondary batteries due to its high specific capacity (3860mAh / g) and low electrode potential (-3.04V). Therefore, using lithium metal directly as the negative electrode material of secondary batteries is the dream of many material experts and scientific researchers.

[0003] The mechanism of action of the metal lithium negative electrode in the battery is the deposition and dissolution of metal lithium, and its basic reaction formula is: Charging: Li + +e=Li; discharge: Li-e=Li + Unlike conventional lithium-ion battery negative electrodes, what happens is that lithium ions are embedded in and extracted from the graphite negative electrode.

[0004] The growth of lithium dendrites and the rupture, generation and continuous accumulation of SEI films on the surface of lithium metal have always restricted the practical application of metallic lithium. In order to solve the problem of lithium dendrites, the existing technology generally uses 3D current collectors with high specific surface area to load metallic lithium, thereby fully reducing the apparent current density of the electrode. For example, Chao Shen's research group at Northwestern Polytechnical University [K. Xie, W. Wei, K. Yuan, W. Lu, M. Guo, Z. Li, Q. Song, X.-R. Liu, J.-G. Wang, C. Shen, Towards dendrite-free lithium deposition via structural and interfacial synergistic effects of 3D graphene@Ni scaffold, Acs Appl Mater Inter 8(39)(2016)26091-26097.] used graphene-modified nickel foam as the working electrode and achieved a stable cycle of 100 cycles at a current density of 1 mA / cm2. Similarly, the research group of Quan-Hong Yang of Tsinghua University in Shenzhen [Q. Yun, Y.-B. He, W. Lv, Y. Zhao, B. Li, F. Kang, Q.-H. Yang, Chemical dealloying derived 3D porous current collector for Li metal anodes, Advanced Materials 28 (32) (2016) 6932-6939.] used porous copper obtained by dealloying as the current collector and achieved 150 stable cycles at a current density of 1 mA / cm2. However, the high specific surface area of ​​the 3D current collector leads to a large number of interfacial reactions, which causes the 3D current collector to generate a large amount of SEI film, resulting in a large amount of consumption of active metal lithium and electrolyte. More seriously, this SEI film continues to expand during the continuous lithium deposition process, and will continue to shrink during the lithium dissolution process. As the cycle progresses, this SEI film will rupture, and will continue to generate and accumulate, resulting in an increase in battery polarization and a decrease in capacity, and even causing safety accidents.

[0005] Therefore, constructing a stable SEI film is an important step to realize the industrial application of metallic lithium. For example, Yunhui Huang's research group at Huazhong University of Science and Technology [J. Xiang, Y. Zhao, L. Yuan, C. Chen, Y. Shen, F. Hu, Z. Hao, J. Liu, B. Xu, Y. Huang, A strategy of selective and dendrite-free lithium deposition for lithium batteries, Nano Energy 42 (2017) 262-268.] used hollow carbon materials coated with Nafion layers as current collectors and achieved 80 stable cycles at a current density of 2 mA / cm2. However, during the continuous cycling process, the SEI film is constantly squeezed and shrunk due to the deposition and dissolution of lithium, which will eventually make it difficult for the cycling performance of lithium metal batteries to meet the requirements of practical applications. Summary of the invention

[0006] In order to solve the problem that existing lithium metal batteries are prone to the generation of lithium dendrites and unstable SEI films, which lead to poor battery performance, the first purpose of the present invention is to provide a current collector for metal lithium batteries, aiming to solve the problems of lithium dendrites and poor stability of SEI films, so as to achieve the purpose of improving its electrical performance.

[0007] The second object of the present invention is to provide a method for preparing the current collector for the metal lithium battery.

[0008] The third object of the present invention is to provide an application of the current collector in a lithium metal battery.

[0009] The fourth object of the present invention is to provide a lithium metal negative electrode for a secondary lithium battery, which is intended to overcome lithium dendrites, enhance the stability of the SEI film, and improve the electrical performance of the lithium metal battery, especially the high current density (2-5 mA / cm 2 ) under cycle performance.

[0010] The fifth object of the present invention is to provide a method for preparing the metallic lithium negative electrode of the secondary lithium battery.

[0011] The sixth objective of the present invention is to provide an application of the metal lithium negative electrode of the secondary lithium battery.

[0012] A current collector for a metal lithium battery, comprising a planar metal current collector, wherein the planar metal current collector has a first surface and a second surface;

[0013] The planar metal current collector is provided with a plurality of channels that penetrate the first surface and the second surface and are independent of each other, and the cross section of the channels is rectangular;

[0014] The metal on the first surface and / or the second surface of the planar metal current collector is composited with an insulating layer A.

[0015] An insulating layer B is composited on the metals of any two opposite surfaces in the channel.

[0016] The planar metal current collector described in the present invention is a flat layered structure, which has an upper plane and a lower bottom surface (that is, the first surface and the second surface, which can also be understood as a surface perpendicular to the thickness direction). The present invention innovatively sets a number of through-holes along the thickness direction of the planar metal current collector, and innovatively sets the shape of the holes and the insulating layers A and B; such a setting can fully reduce the apparent current density and also regulate the metal lithium growth interface. The current collector described in the present invention is conducive to ensuring that the SEI film floats up and down in the hole during the deposition and dissolution of metal lithium, effectively avoiding the extrusion or even rupture of the SEI film during the deposition / dissolution of the traditional 3D lithium metal negative electrode; it can significantly improve the electrical performance of lithium metal batteries, especially the cycle performance under high current density.

[0017] The planar metal current collector is a metal foil, and its material is preferably at least one of copper, titanium, nickel, iron and chromium.

[0018] More preferably, the metal current collector is any one of single metal current collectors such as copper foil, titanium foil, nickel foil, iron foil, chromium foil, and their binary or ternary alloy foils, and their composition ratio is arbitrary; preferably copper foil.

[0019] The thickness of the metal current collector is 5 to 500 μm.

[0020] Preferably, the thickness of the metal current collector is 15-100 μm.

[0021] Preferably, the porosity is 10-90%, preferably 30-80%. Under the preferred porosity, the current collector can have good mechanical strength and toughness, and can achieve uniform lithium deposition and dissolution at high current density and high area capacity.

[0022] More preferably, the porosity is 40-60%.

[0023] The first surface or the second surface refers to a surface perpendicular to the thickness direction. When assembling the battery, the first surface or the second surface and the diaphragm are arranged opposite to each other.

[0024] Preferably, the pores are perpendicular to the surface of the planar metal current collector, that is, the pores penetrate the planar metal current collector along the thickness direction.

[0025] The cross section of the pore (a plane parallel to the first surface or the second surface of the planar current collector) is a rectangle; the four sides of the rectangle may be the same or different; preferably, they are different.

[0026] Preferably, the width of the channel (referring to the width of the cross section) is 1 to 30 μm, and more preferably 5 to 20 μm.

[0027] Preferably, the length of the channel (referring to the length of the cross section) is 3 to 50 μm, and more preferably 8 to 40 μm.

[0028] Preferably, the length-to-width ratio of the pores is 1 to 5:1, preferably 1.5 to 3:1.

[0029] The holes are arranged independently of each other, which can further reduce the interface reaction and help to further improve the electrical performance.

[0030] Preferably, the pores have a smooth surface, which is conducive to uniform nucleation of metallic lithium, and then to the formation of a uniform and stable SEI film, so that subsequent metallic lithium deposition and dissolution are uniform.

[0031] Preferably, the metals on the two surfaces with large areas in the pores are compounded with an insulating layer B. That is, except for the two surfaces with smaller areas in the pores of the planar metal current collector, all other metal surfaces are compounded with insulating materials. Such a configuration is conducive to ensuring that the SEI film floats up and down on the wide surface (surface with smaller area) during the deposition and dissolution of metallic lithium, thereby avoiding the extrusion and rupture of the SEI film during the deposition and dissolution of lithium.

[0032] Coating the long surface (surface with a larger area) with an insulating layer B allows lithium to be deposited only on the wide surface of the rectangular channel. The initial deposition of lithium metal is accompanied by the formation of surface SEI, and then the metal lithium continues to deposit under the SEI film. Selecting to deposit lithium on the wide surface can effectively reduce the amount of SEI formed, and then effectively reduce the loss of active lithium, and ultimately improve the cycle performance of the battery.

[0033] Preferably, the material of the insulating layers A and B is at least one of polyvinyl alcohol, polytetrafluoroethylene, polyethylene, polypropylene, polybutylene, polyisobutylene, polyvinylidene chloride, polyvinylidene fluoride, polyethylene terephthalate and polystyrene.

[0034] Preferably, the insulating layers A, B are made of the same material.

[0035] Preferably, the thickness of the insulating layer A is 0.0001 to 0.006 times that of the planar current collector; preferably 0.02 to 3 μm; preferably 0.05 to 2 μm; further preferably 0.1 to 0.5 μm.

[0036] Preferably, the thickness of the insulating layer B is less than 0.001 to 0.05 times the width of the channel, preferably 0.02 to 1.5 μm, preferably 0.05 to 1.2 μm, and more preferably 0.1 to 0.5 μm.

[0037] In the present invention, the pores of the current collector are obtained by focused ion beam etching technology.

[0038] The present invention provides a method for preparing the current collector for a metal lithium battery, wherein the pores are formed by etching on the planar metal current collector by a focused ion beam etching method; then, a polymer of an insulating layer is coated to form insulating layers A and B; and the current collector for a metal lithium battery is obtained.

[0039] In the field of lithium metal anode of the present invention, lithium deposition is carried out in an organic electrolyte, which has a greater viscosity than an aqueous electrolyte. The etching process must consider the wettability of the organic electrolyte, the uniformity of metal lithium deposition, and the apparent area and mechanical strength in the subsequent electrodeposition process. In order to obtain materials that are innovatively suitable for lithium metal anodes, the present invention innovatively utilizes focused ion beam etching technology, and innovatively finds that materials that meet the requirements of lithium metal anodes can be obtained by controlling the etching voltage and etching time.

[0040] Preferably, the etching voltage is 3-40 kV, preferably 5-30 kV. If the etching voltage is low, the etching is slow, which is not conducive to improving the working efficiency. If the voltage is too high, it is easy to burn the surface of the working electrode, which is not conducive to preparing a working electrode with a smooth surface.

[0041] More preferably, the etching voltage is 10-20 kV.

[0042] Preferably, the etching time is 0.2 to 10 hours; preferably 0.5 to 7 hours. If the etching time is too short, the pores are too shallow, which is not conducive to increasing the surface area of ​​the working electrode, and can only store a small amount of metallic lithium. If the etching time is too long, the pores are very large, which is also not conducive to increasing the surface area of ​​the working electrode, and too large pores will greatly reduce the mechanical strength of the electrode.

[0043] More preferably, the etching time is 1 to 4 hours.

[0044] The insulating layer may be formed by a coating method, for example, by slurrying the material of the insulating layer and then coating it.

[0045] The present invention also provides an application of the current collector for a metal lithium battery, which is used to prepare a lithium metal negative electrode. In the application, the existing method is used to fill the pores with metal lithium to prepare the lithium metal negative electrode.

[0046] The present invention also provides a metal lithium negative electrode of a secondary lithium battery, comprising the current collector and metal lithium filled in the pores of the current collector.

[0047] The present invention discloses a metal lithium negative electrode for a secondary lithium battery, which is composed of a planar metal current collector rich in vertical rectangular micron-pores, an insulating layer uniformly covering the upper surface (first surface or second surface) of the planar metal current collector and the long surface (large surface) of the rectangular micron-pores, and metal lithium filled in the rectangular micron-pores.

[0048] The lithium metal negative electrode described in the present invention has a high working area provided by the pores, which is beneficial to the battery cycle at a high current density. At the same time, the insulating layer A covering the upper surface of the metal current collector prevents lithium from preferentially depositing near the surface of the diaphragm. In addition, the insulating layer B covering the long surface of the rectangular micron pore (the surface with a larger area) is beneficial to the deposition of metal lithium on the wide surface (the surface with a smaller area) of the micron pore, which is beneficial to ensure that the SEI film floats up and down in the pore (preferably on the wide surface) during the deposition and dissolution of metal lithium, thereby avoiding the extrusion and rupture of the SEI film during the deposition and dissolution of lithium. The metal lithium negative electrode designed in this way can achieve ultra-stable and ultra-long-term circulation.

[0049] Preferably, the content of metallic lithium is 12 to 88 vol.%, and more preferably 32 to 78 vol.%.

[0050] The present invention also provides a method for preparing the metal lithium negative electrode of the secondary lithium battery, wherein metal lithium is filled into the current collector pores by an electrodeposition or melting method to prepare the metal lithium negative electrode.

[0051] Preferably, the pores are filled with metallic lithium by electrodeposition.

[0052] Preferably, the electrodeposition step is: using the current collector as a working electrode and the lithium sheet as a counter electrode, and performing electrodeposition in an organic solvent containing a lithium salt.

[0053] The amount of electrodeposited metallic lithium is 2 to 12 mAh / cm2, and more preferably 5 to 8 mAh / cm2.

[0054] The present invention also provides an application of the metal lithium negative electrode, which is used as a negative electrode and assembled with a positive electrode, a separator and an electrolyte to obtain a lithium metal battery.

[0055] The present invention also provides a lithium metal battery loaded with the lithium metal negative electrode.

[0056] Preferably, the lithium metal battery is a lithium sulfur battery, a lithium iodine battery, a lithium selenium battery, a lithium tellurium battery, a lithium oxygen battery or a lithium carbon dioxide battery.

[0057] When assembling the battery, the button cell is coated on one side with the insulating layer A. During the battery assembly process, the insulating layer A side is close to the separator.

[0058] For soft-pack batteries, the insulating layer A is coated on both sides.

[0059] Beneficial effects:

[0060] The proposed metal lithium negative electrode for high-energy secondary lithium batteries has a vertical rectangular micron-pore with a high specific surface area, which is conducive to fully reducing the apparent current density. The presence of the insulating layer on the surface of the metal current collector and the insulating layer on the long surface (surface with a large area) of the rectangular micron-pore can effectively prevent the growth of metal lithium at these interfaces, so that the metal lithium can fully grow on the wide surface of the rectangular micron-pore. This design is conducive to ensuring that the SEI film floats up and down on the wide surface during the deposition and dissolution of metal lithium, effectively avoiding the extrusion or even rupture of the SEI film during the deposition / dissolution of the traditional 3D lithium metal negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of titanium foil modified with vertical rectangular micro-channels in Example 1.

[0062] Figure 2 Schematic diagram of the titanium foil with vertical rectangular micro-channels modified with polyethylene in Example 1.

[0063] Figure 3 This is a graph showing the cycling performance of the titanium foil in Example 1, the titanium foil modified with vertical rectangular micro-channels, and the titanium foil modified with vertical rectangular micro-channels of polyethylene.

[0064] Figure 4 Schematic diagram of the titanium foil with vertical rectangular micro-channels modified with polyethylene after lithium deposition in Example 3.

[0065] Among them, 1 is a metal substrate; 2 is a vertical rectangular micron channel; 3 is an insulating layer A; 4 is an insulating layer B; and 5 is metallic lithium. DETAILED DESCRIPTION

[0066] The following is a specific description of the preferred embodiments of the present invention, which does not constitute any limitation to the present invention. That is, the present invention is not meant to be limited to the above embodiments, and common modifications or alternative compounds in the technical field are all included in the scope defined by the claims of this application.

[0067] Example 1

[0068] A clean titanium foil (15 μm) was placed under a focused ion beam and etched into vertical micro-channels with a width of 6 μm and a length of 12 μm. The porosity was 65% ( Figure 1). The etching time is 1h and the etching voltage is 15kV. The upper surface of the etched titanium foil is coated with an insulating layer A (0.1μm) and the long surface of the rectangular vertical micron channel is coated with an insulating layer B (0.1μm) (both insulating layers A and B are composed of polyethylene, in which polyethylene particles are dispersed in nitrogen methyl pyrrolidone) ( Figure 2 The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and 1M LiTFSI / DOL∶DME (volume ratio = 1:1) containing 3wt.% LiNO3 was used as the electrolyte to assemble the button cell and perform the charge-discharge cycle test. At the same time, the pure titanium foil and the titanium foil modified with vertical rectangular micro-channels were used as common comparison samples to perform the corresponding charge-discharge cycle test.

[0069] Tests have found that at 2mA / cm 2 At current densities of 1.3 and 1.7 MHz, the cycle life of the titanium foil with vertical rectangular micro-channels modified by polyethylene is more than 9 times that of the pure titanium foil, and the cycle life of the titanium foil with vertical rectangular micro-channels modified by polyethylene is more than 4 times that of the pure titanium foil. Figure 3 ). The relevant specific data are in Table 1.

[0070] Example 2

[0071] A clean nickel-iron alloy foil (55 μm) was placed under a focused ion beam to etch a vertical micron channel with a width of 9 μm and a length of 24 μm, and the porosity was 55%. The etching time was 4 hours and the etching voltage was 12 kV. The nickel-iron alloy foil after etching was coated with an insulating layer A (0.3 μm) on the upper surface and an insulating layer B (0.1 μm) on the long surface of the rectangular vertical micron channel (both insulating layers A and B were composed of polytetrafluoroethylene, wherein polytetrafluoroethylene particles were dispersed in nitrogen methyl pyrrolidone) with a brush. The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled with 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the charge and discharge cycle test was carried out. At the same time, the pure nickel-iron alloy foil and the nickel-iron alloy foil modified with vertical rectangular micron channels were used as common comparison samples for the corresponding charge and discharge cycle test.

[0072] Tests have found that at 4mA / cm 2 At a current density of 1.17 W / m, the cycle life of the nickel-iron alloy foil with vertical rectangular micro-channels modified by polytetrafluoroethylene is more than 8 times that of the pure nickel-iron alloy foil, and more than 5 times that of the nickel-iron alloy foil modified by vertical rectangular micro-channels. The relevant specific data are shown in Table 1.

[0073] Table 1

[0074]

[0075] Example 3

[0076] The titanium foil with vertical rectangular micro-pores modified with polyethylene in Example 1 was used as the working electrode and then 2 At a current density of 6 mAh / cm 2 Metal lithium is added to the electrode to prepare a composite negative electrode material ( Figure 4 ), and then formed a lithium-sulfur battery with a S-rich nitrogen-doped graphene positive electrode, and carried out charge and discharge cycle tests at 1C in an electrolyte of 1M LiTFSI / DOL∶DME (volume ratio = 1:1) containing 3wt.% LiNO3.

[0077] Comparative Example 1

[0078] This comparative example discusses the use of a planar current collector, as follows:

[0079] Pure titanium foil was used as the working electrode and then 2 At a current density of 6 mAh / cm 2 The metallic lithium was deposited on titanium foil to prepare a lithium-containing titanium foil negative electrode material, which was then combined with a S-rich nitrogen-doped graphene positive electrode to form a lithium-sulfur battery. The charge and discharge cycle test was carried out in an electrolyte of 1MLiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3.

[0080] Comparative Example 2

[0081] This comparative example discusses that the planar current collector is etched, but the insulating layer is not compounded, as follows:

[0082] The titanium foil with vertical rectangular micro-pores obtained in Example 1 was used as the working electrode and then 2 At a current density of 6 mAh / cm 2 Metallic lithium is added to the electrode to prepare a lithium-containing negative electrode material, which is then combined with a S-rich nitrogen-doped graphene positive electrode to form a lithium-sulfur battery. The charge and discharge cycle test was carried out in an electrolyte of 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3.

[0083] The test results of the prepared batteries are shown in Appendix 2.

[0084] Table 2

[0085]

[0086] Comparison of Example 3 with Comparative Examples 1 and 2 shows that the coulombic efficiency and cyclability of the lithium anode of the present invention are significantly improved.

[0087] Example 4

[0088] Clean copper foil, titanium foil, nickel foil, iron foil, and chromium foil (25 μm) were placed under a focused ion beam to etch vertical micrometer channels with a width of 10 μm and a length of 25 μm, and the porosity was 65%. The etching time was 2 hours and the etching voltage was 18 kV. The etched copper foil, titanium foil, nickel foil, iron foil, and chromium foil were coated with an insulating layer A (0.5 μm) on the upper surface and an insulating layer B (0.12 μm) on the long surface of the rectangular vertical micrometer channels with a brush (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled using 1MLiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3 as the electrolyte, and the voltage was 5 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 3.

[0089] Table 3

[0090]

[0091] The results show that the current collector prepared from copper foil exhibits the best performance, followed by nickel foil and iron foil, and the worst are chromium foil and titanium foil.

[0092] Example 5

[0093] A clean copper foil (25 μm) was placed under a focused ion beam and two types of square channels were etched out. The first type was 10 μm in length and width, and the second type was 25 μm in length and width, with a porosity of 65%. The etching time was 2 h and the etching voltage was 18 kV. The etched copper foil was coated with an insulating layer A (0.5 μm) on the upper surface and an insulating layer B (0.12 μm) on any two opposite sides of the rectangular vertical micron channel using a brush (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen-methylpyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3 wt.% LiNO3 as the electrolyte, and the electrode was charged at 5 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 4.

[0094] Table 4

[0095]

[0096]

[0097] Comparison of the results of Examples 4 and 5 shows that the performance of etching square channels is slightly worse than that of etching rectangular channels.

[0098] Example 6

[0099] Experimental example of compounding on a small surface

[0100] A clean copper foil (25 μm) was placed under a focused ion beam to etch vertical micrometer channels with a width of 10 μm and a length of 25 μm, and the porosity was 65%. The etching time was 2 hours and the etching voltage was 18 kV. The etched copper foil was coated with an insulating layer A (0.5 μm) on the upper surface and an insulating layer B (0.12 μm) on the wide surface of the rectangular vertical micrometer channels using a brush (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen-methylpyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3 as the electrolyte, and the electrode was charged at 5 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 5.

[0101] Table 5

[0102]

[0103] Comparison of the results of Examples 4 and 6 shows that the performance of the wide-side coated insulation layer is slightly inferior to that of the long-side coated insulation layer.

[0104] Example 7

[0105] A clean iron foil (50 μm) was placed under a focused ion beam and etched into holes with a length of 30 μm and a width of 16 μm, respectively, with porosities of 5%, 20%, 40%, 60%, 85% and 95%, respectively. The etching time was 2.2 h and the etching voltage was 25 kV. The etched copper foil was coated with an insulating layer A (0.4 μm) on the upper surface and an insulating layer B (0.1 μm) on the long side of the rectangular vertical micron-channel using a brush (both insulating layers A and B were composed of polyvinylidene chloride, in which polyvinylidene chloride particles were dispersed in nitrogen methyl pyrrolidone). The electrodes obtained after drying were used as working electrodes, and a metal lithium sheet was used as a counter electrode. A button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3 as the electrolyte, and the electrode was charged at 3 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 6.

[0106] Table 6

[0107]

[0108] The results show that the performance of the obtained electrode is optimal within the preferred porosity range.

[0109] Example 8

[0110] A clean copper-nickel alloy foil (80 μm) was placed under a focused ion beam to etch vertical micro-channels with a width of 10 μm and a length of 25 μm, and the porosity was 50%. The etching time was set to 0.1, 0.3, 1, 4, 8.5, and 15 h, respectively, and the etching voltage was 25 kV. The copper-nickel alloy foil after etching was coated with an insulating layer A (1.4 μm) on the upper surface and an insulating layer B (0.3 μm) on the long side of the rectangular vertical micro-channel with a brush (both insulating layers A and B were composed of polytetrafluoroethylene, in which polytetrafluoroethylene particles were dispersed in nitrogen methyl pyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled with 1MLiTFSI / DOL:DME (volume ratio = 1:1) containing 2wt.% LiNO3 as the electrolyte, and the electrode was charged at 3 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 7.

[0111] Table 7

[0112]

[0113]

[0114] The results show that the performance of the electrode obtained is optimal within the preferred etching time range of 1 to 4 hours.

[0115] Example 9

[0116] A clean copper-iron alloy foil (120 μm) was placed under a focused ion beam to etch vertical micrometer channels with a width of 12 μm and a length of 28 μm, and the porosity was 60%. The etching time was set to 7 h, and the etching voltage was 2, 4, 10, 20, 35, and 50 kV. The etched copper-nickel alloy foil was coated with an insulating layer A (2 μm) on the upper surface and an insulating layer B (0.3 μm) on the long surface of the rectangular vertical micrometer channel using a brush (both insulating layers A and B were composed of polyvinylidene fluoride, in which polyvinylidene fluoride particles were dispersed in nitrogen methyl pyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 2wt.% LiNO3 as the electrolyte, and the battery was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 8.

[0117] Table 8

[0118]

[0119] The results show that the performance of the obtained electrode is optimal within the preferred etching voltage range.

[0120] Example 10

[0121] A clean iron foil (120 μm) was placed under a focused ion beam to etch vertical micrometer channels with a width of 10 μm and a length of 28 μm, and the porosity was 50%. The etching time was set to 6 h and the etching voltage was 24 kV. The etched iron foil was coated with an insulating layer A (1 μm) on the upper surface and an insulating layer B (the thickness of the insulating layer B was set to 0.01, 0.03, 0.1, 0.05, 1.3, 2 μm) on the long surface of the rectangular vertical micrometer channel using a brush pen (both the insulating layers A and B were composed of polyvinylidene fluoride, in which polyvinylidene fluoride particles were dispersed in nitrogen methyl pyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled using 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 2wt.% LiNO3 as the electrolyte, and the reaction was carried out at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 9.

[0122] Table 9

[0123]

[0124] The results show that when the thickness of the insulating layer B is in the preferred range of 0.1 to 0.5 μm, the performance of the obtained electrode is optimal.

[0125] Embodiment 11

[0126] A clean chromium foil (100 μm) was placed under a focused ion beam to etch vertical micrometer channels with a width of 10 μm and a length of 28 μm, and the porosity was 55%. The etching time was set to 6 h and the etching voltage was 20 kV. The etched chromium foil was coated with an insulating layer A on the upper surface with a brush (the thickness of the insulating layer A was set to 0.01, 0.03, 0.1, 1, 1.5, 4 μm) and the long surface of the rectangular vertical micrometer channel was coated with an insulating layer B (0.12 μm) (both the insulating layers A and B were composed of polyvinylidene fluoride, in which polyvinylidene fluoride particles were dispersed in nitrogen methyl pyrrolidone). The electrode obtained after drying was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled with 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 2wt.% LiNO3 as the electrolyte, and the reaction was carried out at 5 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 10.

[0127] Table 10

[0128]

[0129]

[0130] The results show that when the thickness of the insulating layer A is in the preferred range of 0.1 to 0.5 μm, the performance of the obtained electrode is optimal.

[0131] Example 12

[0132] The titanium foil with vertical rectangular micro-pores modified with polyethylene in Example 1 was used as the working electrode and then 2 At current densities of 1, 3, 5, 7, 10, and 15 mAh / cm 2 Metal lithium was added to the electrode to prepare a composite negative electrode material, and then a lithium-sulfur battery was formed with a nitrogen-doped mesoporous carbon positive electrode rich in sulfur. A charge-discharge cycle test was performed at 1C in an electrolyte of 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3. The relevant test results are shown in Table 11.

[0133] Table 11

[0134]

[0135] The results show that the optimal range is 5 to 8 mAh / cm 2 The performance of the obtained electrode is optimal within the range of deposited lithium amount.

[0136] Comparative Example 3

[0137] A 3D current collector is used, as follows:

[0138] A clean copper foil (30 μm) was placed under a focused ion beam and etched into vertical micro-channels with a width of 10 μm and a length of 30 μm, and the porosity was 65%. The etching time was set to 6 h and the etching voltage was 24 kV. The copper foil was used as the working electrode, the metal lithium sheet was used as the counter electrode, and the button cell was assembled with 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the electrode was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0139] Comparative Example 4

[0140] The plane etching is not through, as follows:

[0141] Under the conditions of Comparative Example 3, a porous copper electrode without through-holes was prepared. It was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3 as the electrolyte. The battery was charged at 4mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0142] Comparative Example 5

[0143] No insulating layer is provided in the hole, as follows:

[0144] A clean copper foil (30 μm) was placed under a focused ion beam to etch vertical micron channels with a width of 10 μm and a length of 30 μm, and the porosity was 65%. The etching time was set to 6 h, and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer A (0.1 μm) on the upper surface with a brush (the insulating layer A was composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the battery was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0145] Comparative Example 6

[0146] No insulation layer on the surface

[0147] A clean copper foil (30 μm) was placed under a focused ion beam to etch out vertical micrometer channels with a width of 10 μm and a length of 30 μm, and the porosity was 65%. The etching time was set to 6 h, and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer B (0.1 μm) on the four sides of the rectangular vertical micrometer channels with a brush (the insulating layer B was composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the battery was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0148] Comparative Example 7

[0149] A clean copper foil (30 μm) was placed under a focused ion beam to etch a vertical micron channel with a width of 10 μm and a length of 30 μm, and the porosity was 65%. The etching time was set to 6 h and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer A (0.1 μm) on the upper surface with a brush and an insulating layer B (0.1 μm) was coated on the two wide sides and one long side of the rectangular vertical micron channel (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the battery was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0150] Comparative Example 8

[0151] A clean copper foil (30 μm) was placed under a focused ion beam to etch a vertical micron channel with a width of 10 μm and a length of 30 μm, and the porosity was 65%. The etching time was set to 6 h and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer A (0.1 μm) on the upper surface with a brush and an insulating layer B (0.1 μm) was coated on the two long faces and one wide face of the rectangular vertical micron channel (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL∶DME (volume ratio = 1∶1) containing 3wt.% LiNO3 as the electrolyte, and the battery was operated at 4 mA / em 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0152] Comparative Example 9

[0153] The cross section of the hole is circular:

[0154] A clean copper foil (30 μm) was placed under a focused ion beam to etch a vertical micron channel with a diameter of 10 μm and a porosity of 65%. The etching time was set to 6 h and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer A (0.1 μm) on the upper surface and an insulating layer B (0.1 μm) on a semicircular surface of the circular vertical micron channel using a brush (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as a working electrode, a metal lithium sheet was used as a counter electrode, and a button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3 wt.% LiNO3 as the electrolyte, and the electrode was charged at 4 mA / cm2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0155] Comparative Example 10

[0156] The cross section of the hole is circular:

[0157] A clean copper foil (30 μm) was placed under a focused ion beam to etch a vertical micron channel with a diameter of 30 μm and a porosity of 65%. The etching time was set to 6 h and the etching voltage was 24 kV. The etched copper foil was coated with an insulating layer A (0.1 μm) on the upper surface with a brush and an insulating layer B (0.1 μm) was coated on a semicircular surface of the circular vertical micron channel (both insulating layers A and B were composed of polypropylene, in which polypropylene particles were dispersed in nitrogen methyl pyrrolidone). After drying, it was used as the working electrode, a metal lithium sheet was used as the counter electrode, and a button cell was assembled using 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 3wt.% LiNO3 as the electrolyte, and the electrode was charged at 4 mA / cm 2 The charge and discharge cycle test was carried out at a current density of . The relevant results of the test are shown in Table 12.

[0158] Table 12

[0159]

[0160] It is found through the above embodiments and comparative examples that the electrical performance of the obtained battery can be improved under the structure of the present invention and the setting of the insulating layer.

Claims

1. A current collector for a metal lithium battery, characterized in that: A planar metal current collector is provided, wherein the planar metal current collector has a first surface and a second surface; The planar metal current collector is provided with a plurality of channels that penetrate the first surface and the second surface and are independent of each other, and the cross-section of the channels is rectangular; the planar metal current collector is a metal foil, and its material is at least one of copper, titanium, nickel, iron, and chromium; the channels are perpendicular to the surface of the planar metal current collector; The metal on the first surface and / or the second surface of the planar metal current collector is composited with an insulating layer A. An insulating layer B is compounded on the metals of the two surfaces with a large area in the hole.

2. The current collector for a metal lithium battery according to claim 1, characterized in that: The thickness of the planar metal current collector is 5-500 μm.

3. The current collector for a metal lithium battery according to claim 1, characterized in that: The thickness of the planar metal current collector is 15-100 μm.

4. The current collector for a metal lithium battery according to claim 1, characterized in that: The porosity of the planar metal current collector is 10-90%.

5. The current collector for a metal lithium battery according to claim 1, characterized in that: The porosity of the planar metal current collector is 30-80%.

6. The current collector for a metal lithium battery according to claim 1, characterized in that: The porosity of the planar metal current collector is 40-60%.

7. The current collector for a metal lithium battery according to claim 1, characterized in that: The pores have a smooth surface.

8. The current collector for a metal lithium battery according to claim 1, characterized in that: The width of the pores is 1~30 µm and the length is 3~50 µm.

9. The current collector for a metal lithium battery according to claim 1, characterized in that: The length-to-width ratio of the hole is 1~5:

1.

10. The current collector for a metal lithium battery according to claim 1, characterized in that: The length-to-width ratio of the pores is 1.5~3:

1.

11. The current collector for a metal lithium battery according to any one of claims 1 to 10, characterized in that: The material of the insulating layers A and B is at least one of polyvinyl alcohol, polytetrafluoroethylene, polyethylene, polypropylene, polybutylene, polyisobutylene, polyvinylidene chloride, polyvinylidene fluoride, polyethylene terephthalate, and polystyrene; The thickness of the insulating layer A is 0.0001 to 0.006 times that of the planar metal current collector; The thickness of the insulating layer B is less than 0.001 to 0.05 times the width of the hole.

12. The current collector for a metal lithium battery according to claim 11, characterized in that: The thickness of the insulating layer A is 0.02~3µm; The thickness of the insulating layer B is smaller than the width of the hole and is 0.02~1.5 µm.

13. The current collector for a metal lithium battery according to claim 12, characterized in that: The thickness of the insulating layer A is 0.05~2µm; The thickness of the insulating layer B is smaller than the width of the hole by 0.05~1.2 µm.

14. The current collector for a metal lithium battery according to claim 13, characterized in that: The thickness of the insulating layer A is 0.1~0.5µm; The thickness of the insulating layer B is 0.1~0.5 µm.

15. A method for preparing a current collector for a metal lithium battery according to any one of claims 1 to 14, characterized in that: The pores are formed by etching the planar metal current collector by a focused ion beam etching method; then the polymer of the insulating layer is coated to form insulating layers A and B; and the current collector for the metal lithium battery is obtained.

16. The method for preparing a current collector for a metal lithium battery according to claim 15, characterized in that: The etching voltage is 3~40 kV.

17. The method for preparing a current collector for a metal lithium battery according to claim 16, characterized in that: The etching voltage is 5~30 kV.

18. The method for preparing a current collector for a metal lithium battery according to claim 15, characterized in that: The etching time is 0.2~10 h.

19. The method for preparing a current collector for a metal lithium battery according to claim 18, characterized in that: The etching time is 0.5~7 h.

20. The method for preparing a current collector for a metal lithium battery according to claim 19, characterized in that: The etching time is 1~4h.

21. A metallic lithium negative electrode for a secondary lithium battery, characterized in that: A current collector comprising the current collector according to any one of claims 1 to 14 or the current collector prepared by the preparation method according to any one of claims 15 to 20, and metallic lithium filled in the pores of the current collector; The content of metallic lithium is 12~88 vol.%.

22. The metal lithium negative electrode of the secondary lithium battery according to claim 21, characterized in that: The content of metallic lithium is 32~78 vol.%.

23. A method for preparing a metallic lithium negative electrode of a secondary lithium battery according to claim 21 or 22, characterized in that: The metal lithium negative electrode is prepared by filling the collector pores with metal lithium through an electrodeposition or melting method.

24. The method for preparing a metallic lithium negative electrode of a secondary lithium battery according to claim 23, characterized in that: The pores are filled with metallic lithium by electrodeposition.

25. The method for preparing a metallic lithium negative electrode of a secondary lithium battery according to claim 24, characterized in that: The electrodeposition step is: using the current collector as a working electrode and the lithium sheet as a counter electrode to perform electrodeposition in an organic solvent containing a lithium salt; The amount of electrodeposited metallic lithium is 2~12 mAh / cm2.

26. The method for preparing a metallic lithium negative electrode of a secondary lithium battery according to claim 25, characterized in that: The electrodeposition steps are as follows: the amount of electrodeposited metallic lithium is 5-8 mAh / cm2.

27. A use of the metal lithium negative electrode according to any one of claims 21 to 22, or the metal lithium negative electrode prepared by the preparation method according to any one of claims 23 to 26, characterized in that: It is used as the negative electrode and assembled with the positive electrode, separator and electrolyte to obtain a lithium metal battery.

28. The use according to claim 27, characterized in that: The lithium metal battery is a lithium sulfur battery, a lithium iodine battery, a lithium selenium battery, a lithium tellurium battery, a lithium oxygen battery or a lithium carbon dioxide battery.

Citation Information

Patent Citations

  • Metal lithium battery, and current collector and negative electrode thereof

    CN208923279U